The Effect of Intellectual Capital, Free Cash Flow, and Corporate Social Responsibility (CSR) on Company Value in the Primary Consumer Goods Sector Listed on the Indonesia Stock effect (IDX) in 2021-2023 - Arda Pramesti, Arana (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2025)
Introduction/Main Objectives: This study aims to examine the influence of intellectual capital, free cash flow, and corporate social responsibility (CSR) on firm value among companies listed on the Indonesian Stock Exchange (IDX) from 2021 to 2023. Background Problems: The phenomenon underlying this research is the need to understand the factors affecting firm value, particularly in the primary consumer goods sector, which plays a crucial role in Indonesia's economy. Novelty: This study provides novelty by simultaneously and partially analyzing the effects of intellectual capital, free cash flow, and CSR on firm value. It also utilizes recent data from the 2021–2023 period, reflecting post-COVID-19 business dynamics, which are still rarely explored in this contex. Research Methods: The study employs descriptive and verifiable methods with a quantitative approach. It uses secondary data obtained from the annual and sustainability reports of 34 companies in the primary consumer goods sector listed on the IDX, resulting in 102 observations selected through purposive sampling. The data were analyzed using panel data regression with the E-Views 12 application. Finding/Results & Conclusion: The results show that intellectual capital, free cash flow, and CSR simultaneously affect firm value. Partially, intellectual capital and free cash flow have a significant influence, while CSR does not. Therefore, companies are advised to focus on enhancing intellectual capital and effectively managing free cash flow to increase their market value.